Re-Evaluating the Surface Rupture and Slip Distribution of the AD 1609 M7 1/4 Hongyapu Earthquake Along the Northern Margin of the Qilian Shan, NW China: Implications for Thrust Fault Rupture Segmentation - Huang, Xiongnan; Yang, Xiaoping; Yang, Haibo; Hu, Zongkai; Zhang, Ling (Frontiers in Earth Science, 2021)
The Hexi Corridor is located in the northeastern corner of the Tibetan Plateau, and it is bounded by a series of active thrusts along the northern margin of the Qilian Shan and the southern piedmont of the Longshou Shan. Historically, five destructive earthquakes have occurred along the Hexi Corridor, which indicates that this region poses high potential seismic risks. The 1609 Hongyapu earthquake occurred along the Fodongmiao-Hongyazi fault in the northern Qilian Shan, China, and it killed more than 840 people and destroyed a large number of buildings. Presently, there are different opinions as to the distribution and length of the surface rupture of this event along the Fudongmiao–Hongyazi fault. Thus, we searched all of the lower fault scarps on the Holocene surfaces and suspected surface rupture locations related to the 1609 earthquake based on previous studies and developed detailed remote-sensing interpretations along the fault. An abundance of north dip scarps on the younger fans and terrace faces, slightly higher than the active modern stream bed, were found along the Fodongmiao-Hongyazi fault in the area ranging from the Hongshuiba River in the west to the Shuiguan River in the east. The cumulative fault rupture length was estimated as ~98 km based on the distribution of the fault scarps on Late Holocene surfaces and constraints provided by age dating. Most of the surface ruptures are preserved as fault scarps and indicate an average vertical surface offset of ~1.0 m, a value found consistently in three segments of the fault. The surface rupture features indicate that segments of the fault coalesced and ruptured simultaneously during the 1609 earthquake, i.e., a single segmentation. Using the surface fault traces, dip inferred from previous reflection profiles, a rigidity of 3.3 × 1010 Nm, and dip slip converted from our observations of the offsets, we computed the magnitude of this event as ca. Mw 7.2–Mw 7.4.